Disclosure : sexual predation in a brave new post - p/c world - G. Moylan-Brouff (Law Text Culture, 1995)
Barry Levinson's recent film, Disclosure, examines the impact of anti-discrimination legislation on white middle class America by foregrounding two contentious issues informing the politics of the workplace. Namely, the use and abuse of sexual harassment laws to regulate behaviour between genders, and the implementation of affirmative action protocols to redress gendered inequities in employment practices. However, this project, which underpins both the film and the book from which it is derived, is contaminated from the outset, by a dubious strategy of role reversal, which constitutes the film's departure point for its interrogation of the value of these laws and directives. Thus Michael Douglas's character, Thomas Sanders, becomes the victim of a harassment campaign waged by his unscrupulous and sexually predatory boss - Meredith Johnson (Demi Moore). His quest for justice in relation to charges of sexual harassment brought by Johnson forms the main plot sequence of the film. What this approach conveniently elides, however, is the overwhelming evidence that women constitute a majority of those subjected to sexual harassment in the workplace. In addition, their access to power in this context continues to be circumscribed by dominant patriarchal practices and attitudes towards women.